The interplay between stakeholders, resources and capabilities in climate change strategy: converting barriers into cooperation - Lopes de Sousa Jabbour, Ana Beatriz; Vazquez-Brust, Diego; Chiappetta Jabbour, Charbel Jose; Andriani Ribeiro, Daniela [UNESP] (Wiley-Blackwell, 2020)
This article investigates how organizations deal with drivers and barriers to the adoption of low-carbon operational (LCO) practices and, accordingly, we propose a framework for relationships with stakeholders to guide organizations in orchestrating stakeholders, resources and capabilities to meet the challenges and opportunities arising from climate change. Data was collected through interviews with experts working within companies participating in the Carbon Disclosure Program and the Brazilian GHG Protocol Program. Our findings show that the level of willingness of stakeholders influences how companies select mechanisms to deal with drivers and barriers to LCO practices. Our results, qualified by stakeholder relationships theory and the natural resource-based view, introduce an analytical approach called 'mechanisms of responses' to understand how organizations deal with drivers and barriers in the context of climate change in order to guide companies to adopt LCO practices, strengthen co-operation with stakeholders and develop the required organizational capabilities.
Keywords: barriers; business strategy; climate change; corporate sustainability; drivers